Probabilitas Side Effects of Herbal Medicine di Kota Gorontalo - Tuloli, Teti Sutriyati; Madania, Madania; Tungadi, Robert; Sapiun, Zulfiayu (Jurusan Farmasi Universitas Negeri Gorontalo, 2024)
The probability of side effects of herbal medicine refers to the negative or undesirable impacts that may arise after consuming products made from natural ingredients or plants. This can include various physical reactions, health issues, or unwanted disorders, ranging from mild to severe. It's important to remember that while herbal medicines are often seen as a more natural option, they still have the potential to cause side effects, just like synthetic drugs. The aim of this research is to identify the probability of side effects of herbal medicine. This research is an observational study with a quantitative descriptive research design using a cross-sectional approach. This research method uses the Naranjo Algorithm. The results indicate that based on the assessment of the causality of ADRs, the outcomes obtained are possible (82.47%), probable (10.31%), and doubtful (7.22%).